Preparation method of high-strength mildew-proof bamboo wood

By removing lignin and hemicellulose from bamboo, and modifying it with titanium source and hydrophobic modifier, high-strength anti-mold bamboo is prepared, which solves the problems of poor environmental protection and poor anti-mold effect of existing bamboo materials, and achieves efficient anti-mold and improved mechanical properties of bamboo materials.

CN119589775APending Publication Date: 2025-03-11ZHEJIANG FORESTRY UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411909456.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing bamboo anti-mold technology has poor environmental protection, poor anti-mold effect, insufficient durability and uniform processing, which limits the application of bamboo in the fields of construction, furniture manufacturing and interior decoration.

Method used

By removing some lignin and hemicellulose from the bamboo, impregnation and transesterification reaction between titanium source and anhydrous ethanol, titanium dioxide with hydroxyl group rich on the surface is formed, and then mixed with a hydrophobic modifier, hydrophobic modification and hot pressing treatment are carried out to prepare high-strength anti-mold bamboo.

Benefits of technology

It achieves the efficient anti-mold effect of bamboo, improves the antibacterial and hydrophobic properties of bamboo, enhances the mechanical properties and service life of bamboo, and avoids the use of severely harmful chemical reagents, making it more environmentally friendly and efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207000910000111
    Figure BDA0005207000910000111
Patent Text Reader

Abstract

The invention provides a preparation method of high-strength mildew-proof bamboo wood, and belongs to the technical field of composite materials. According to the method, part of lignin and hemicellulose are removed from bamboo wood, so that the porosity of the bamboo wood can be increased, a modifier can enter pores, and the modification effect is improved; according to the method, titanium dioxide rich in hydroxyl on the surface is formed in situ in a delignification bamboo test piece, then hydrophobic modification is performed, the titanium dioxide rich in hydroxyl on the surface can react with the hydrophobic modifier, the hydrophobic modifier is stably combined on the bamboo, and the antibacterial property and the hydrophobicity of the bamboo are improved through the synergistic effect of the titanium dioxide and the hydrophobic modifier; the mildew-proof effect is further improved; according to the method, the titanium dioxide hydrophobic bamboo sample is preheated, hot-pressed and shaped, the compression ratio of the high-strength mildew-proof bamboo is controlled to be 20-50%, it can be guaranteed that the high-strength mildew-proof bamboo has high compactness, and the high-strength mildew-proof bamboo keeps high mechanical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a method for preparing high-strength and mildew-proof bamboo material. Background Art

[0002] Bamboo is mainly composed of fiber cells, thin-walled cells and vascular bundles, which provide a rich source of nutrition for microorganisms. In addition, bamboo contains a large amount of organic matter, protein, starch and bamboo fiber, which will promote the growth of mold under appropriate humidity and temperature, and the moisture in bamboo can accelerate the growth of microorganisms, causing bamboo to become moldy, performance degradation and shortened service life, thus limiting its application in construction, furniture manufacturing and interior decoration.

[0003] In order to solve the problem of bamboo mold, the existing anti-mold technology can be divided into two categories: 1. Chemical treatment: including impregnation and spraying of anti-mold agents. Commonly used chemical treatment methods such as sodium chlorite impregnation and benzotriazole treatment can effectively reduce the hygroscopicity of bamboo and improve its anti-mold performance. Although chemical anti-mold agents can effectively improve the anti-mold performance of bamboo, many chemicals pose potential risks to the environment and human health. 2. Surface coating: Use waterproof coatings such as silane or polyurethane coatings to enhance the hydrophobicity of bamboo. These coatings form a protective film that blocks the penetration of water, thereby reducing the hygroscopicity of bamboo and the growth of mold. Although surface coatings can enhance the hydrophobicity of bamboo, the durability and adhesion of these coatings are often affected by environmental factors. After long-term use, the coating may peel off or fail, thereby affecting the waterproof effect and anti-mold performance of bamboo. Therefore, the existing anti-mold technology has the problems of poor environmental protection and poor anti-mold effect.

[0004] In order to improve the mechanical strength of bamboo, the existing technologies mainly include chemical modification and physical modification: 1. Chemical modification: By compounding bamboo with polymer materials, the weight gain rate of bamboo can be increased, the equilibrium moisture content can be reduced, and the bending strength and elastic modulus can be enhanced. However, some polymer materials may have an extraction effect on hemicellulose in bamboo, reduce the integrity of the cell wall structure, and cause cell wall stratification, which limits the application of this method. 2. Physical modification: Ultra-high temperature rapid hot pressing treatment is used to improve the physical and mechanical properties of bamboo by optimizing different temperatures, times and pressures. However, although this method, such as ultra-high temperature rapid hot pressing treatment, can improve dimensional stability and physical and mechanical properties, the distribution of temperature and pressure may be uneven during the hot pressing process, resulting in uneven distribution of strength and density of bamboo, affecting the bending strength and stability of the final product. At the same time, too high a compression rate may cause the vascular bundles and cell walls in the bamboo to rupture, making the material fragile, thereby affecting its bending resistance. The increased brittleness of bamboo makes it easy to break when subjected to force.

[0005] It can be seen that although the existing technology has made some progress in improving the mechanical strength and mildew resistance of bamboo, there are still problems such as environmental and health risks, insufficient durability and processing uniformity. Therefore, in order to improve the application scope and sustainability of bamboo, it is necessary to explore a more environmentally friendly, efficient and stable preparation method of high-strength mildew-resistant bamboo. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a high-strength mildew-resistant bamboo material which is more environmentally friendly, efficient and stable.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing high-strength and mildew-resistant bamboo material, comprising the following steps:

[0009] (1) removing part of the lignin and hemicellulose from the bamboo to obtain a delignified bamboo specimen;

[0010] (2) immersing the delignified bamboo specimen obtained in step (1) in an immersion solution, and then performing an ester exchange reaction to obtain a titanium dioxide-modified bamboo specimen; the immersion solution is a solution composed of a titanium source and anhydrous ethanol;

[0011] (3) mixing the titanium dioxide modified bamboo sample obtained in step (2) with a hydrophobic modifier to perform hydrophobic modification to obtain a titanium dioxide hydrophobic bamboo sample;

[0012] (4) preheating the titanium dioxide hydrophobic bamboo sample obtained in step (3), and then hot pressing and shaping in sequence to obtain a high-strength and mildew-proof bamboo material; the compression rate of the high-strength and mildew-proof bamboo material is 20-50%.

[0013] Preferably, the method for removing part of lignin and hemicellulose from bamboo in step (1) comprises: removing green bamboo and yellow bamboo from fresh bamboo to obtain bamboo; placing the bamboo in a sodium chlorite solution with a pH value of 4 to 5, performing heat treatment, and obtaining a delignified bamboo specimen.

[0014] Preferably, the titanium source in step (2) comprises one or more of tetrabutyl titanate, tetraisopropyl titanate and tetraethyl titanate.

[0015] Preferably, in step (2), the volume ratio of the titanium source to anhydrous ethanol is 1:(30-50).

[0016] Preferably, the temperature of the transesterification reaction in step (2) is 100 to 140° C., and the time of the transesterification reaction is 3 to 5 hours.

[0017] Preferably, the hydrophobic modifier in step (3) comprises one or more of octadecyltrimethoxysilane, hexadecyltrimethoxysilane, methyltrimethoxysilane and vinyltrimethoxysilane.

[0018] Preferably, the temperature of the hydrophobic modification in step (3) is 20 to 45° C., and the time of the hydrophobic modification is 4 to 6 hours.

[0019] Preferably, the preheating temperature and the hot pressing temperature in step (4) are 130-160°C.

[0020] Preferably, the hot pressing pressure in step (4) is 4 to 6 MPa, and the hot pressing time is 10 to 20 min.

[0021] Preferably, the shaping method in step (4) comprises: cooling the hot-pressed titanium dioxide hydrophobic bamboo sample to 40-60° C., and the pressure during cooling is 4-6 MPa.

[0022] The invention provides a preparation method of high-strength and mildew-proof bamboo material, comprising the following steps: removing part of lignin and hemicellulose from bamboo material to obtain a delignified bamboo material specimen; immersing the delignified bamboo material specimen in an immersion liquid, and then performing an ester exchange reaction to obtain a titanium dioxide modified bamboo sample; the immersion liquid is a solution composed of a titanium source and anhydrous ethanol; mixing the titanium dioxide modified bamboo sample with a hydrophobic modifier to perform hydrophobic modification to obtain a titanium dioxide hydrophobic bamboo sample; preheating the titanium dioxide hydrophobic bamboo sample, and then performing hot pressing and shaping in sequence to obtain the high-strength and mildew-proof bamboo material; the compression rate of the high-strength and mildew-proof bamboo material is 20-50%. The present invention can increase the porosity of the bamboo by removing part of lignin and hemicellulose from the bamboo, so that the modifier can enter the pores, thereby improving the modification effect; the present invention can immerse the delignified bamboo specimen in an immersion liquid, so that the titanium source and anhydrous ethanol can enter the pores of the delignified bamboo specimen, and in situ form titanium dioxide with rich hydroxyl groups on the surface, and then perform hydrophobic modification. On the one hand, the titanium dioxide has antibacterial properties and can improve the mildew-proof effect of the bamboo; on the other hand, the titanium dioxide with rich hydroxyl groups on the surface can react with the hydrophobic modifier, so that the hydrophobic modifier is stably combined with the bamboo, and the two Synergistic effect, improve the antibacterial property and hydrophobicity of bamboo, and further improve the mildew-proof effect; the present invention can make the titanium dioxide hydrophobic bamboo sample be heated evenly during hot pressing by preheating the titanium dioxide hydrophobic bamboo sample first, and the structure of the bamboo sample after hot pressing is more stable and uniform; and the present invention can maintain the structural stability of the bamboo sample after hot pressing through shaping treatment; the present invention can ensure that the high-strength mildew-proof bamboo has a higher density by controlling the compression rate of the high-strength mildew-proof bamboo to 20-50%, and does not destroy the internal structure of the high-strength mildew-proof bamboo, thereby maintaining higher mechanical properties of the high-strength mildew-proof bamboo. The results of the embodiment show that when the compression rate of the high-strength mildew-proof bamboo prepared by the present invention is 40%, the control effect of the bamboo sample on Aspergillus niger and Trichoderma viride reaches 100%, and the modulus of rupture (MOR) and modulus of elasticity (MOE) of the bamboo reach 225MPa and 17.1GPa respectively. It can be seen that the preparation method provided by the present invention does not use any seriously harmful chemical reagents, is more environmentally friendly, efficient, and can prepare stable high-strength and mildew-resistant bamboo materials. DETAILED DESCRIPTION

[0023] The present invention provides a method for preparing high-strength and mildew-resistant bamboo material, comprising the following steps:

[0024] (1) removing part of the lignin and hemicellulose from the bamboo to obtain a delignified bamboo specimen;

[0025] (2) immersing the delignified bamboo specimen obtained in step (1) in an immersion solution, and then performing an ester exchange reaction to obtain a titanium dioxide-modified bamboo specimen; the immersion solution is a solution composed of a titanium source and anhydrous ethanol;

[0026] (3) mixing the titanium dioxide modified bamboo sample obtained in step (2) with a hydrophobic modifier to perform hydrophobic modification to obtain a titanium dioxide hydrophobic bamboo sample;

[0027] (4) preheating the titanium dioxide hydrophobic bamboo sample obtained in step (3), and then hot pressing and shaping in sequence to obtain a high-strength and mildew-proof bamboo material; the compression rate of the high-strength and mildew-proof bamboo material is 20-50%.

[0028] The present invention removes part of lignin and hemicellulose from bamboo to obtain a delignified bamboo specimen.

[0029] In the present invention, the method for removing part of lignin and hemicellulose from bamboo preferably comprises: removing green bamboo and yellow bamboo from fresh bamboo to obtain bamboo; placing the bamboo in a sodium chlorite solution with a pH value of 4 to 5, performing heat treatment, and obtaining a delignified bamboo specimen.

[0030] The present invention preferably removes green bamboo and yellow bamboo from fresh bamboo to obtain bamboo material.

[0031] In the present invention, the fresh bamboo is preferably 4-6 years old fresh bamboo without mold and rot defects. The present invention uses the above fresh bamboo, which is more conducive to obtaining bamboo with higher strength.

[0032] The present invention has no special limitation on the method for removing the green and yellow bamboo, and any conventional method for removing the green and yellow bamboo can be used.

[0033] After obtaining the bamboo material, the present invention preferably places the bamboo material in a sodium chlorite solution with a pH value of 4 to 5 for heat treatment to obtain a delignified bamboo material specimen.

[0034] In the present invention, the mass concentration of the sodium chlorite solution is preferably 2-4%, more preferably 2-3%. The present invention preferably uses glacial acetic acid to adjust the pH value of the sodium chlorite solution to 4-5. The present invention uses a sodium chlorite solution with a pH value of 4-5 and controls its concentration within the above range, which is more conducive to removing lignin and hemicellulose without causing excessive damage to the main components of the bamboo.

[0035] The present invention does not impose any particular limitation on the amount of the sodium chlorite solution, as long as the bamboo material can be fully immersed in the sodium chlorite solution.

[0036] In the present invention, the temperature of the heat treatment is preferably 75-85°C, more preferably 80-85°C; the time of the heat treatment is preferably 2-4 hours, more preferably 3-4 hours. The present invention can remove part of the lignin and hemicellulose in the bamboo material and increase the porosity of the bamboo material by controlling the cooking within the above time range.

[0037] In the present invention, the mass content of lignin in the delignified bamboo specimen is preferably 18-20%; the mass content of hemicellulose in the delignified bamboo specimen is preferably 8-10%. The present invention controls the mass content of lignin and hemicellulose in the delignified bamboo specimen within the above range, which can increase the porosity of the bamboo.

[0038] In the present invention, after removing part of the lignin and hemicellulose from the bamboo, the obtained bamboo is washed and dried in sequence to obtain a delignified bamboo specimen. The present invention has no particular limitation on the operation method of the washing and drying, and conventional washing and drying methods can be used to fully remove impurities in the bamboo and dry it.

[0039] After obtaining the delignified bamboo specimen, the present invention immerses the delignified bamboo specimen in an immersion liquid, and then performs an ester exchange reaction to obtain a titanium dioxide modified bamboo specimen.

[0040] In the present invention, the impregnation liquid is a solution composed of a titanium source and anhydrous ethanol.

[0041] In the present invention, the titanium source preferably includes one or more of tetrabutyl titanate, tetraisopropyl titanate and tetraethyl titanate, and more preferably tetrabutyl titanate.

[0042] In the present invention, the volume ratio of the titanium source to anhydrous ethanol is preferably 1: (30-50), more preferably 1: 40. The present invention controls the amount of the titanium source and anhydrous ethanol to be within the above range, so that the titanium source can fully react to form titanium dioxide.

[0043] In the present invention, the method for preparing the impregnation solution is preferably to stir the titanium source and anhydrous ethanol at 200-300 rpm for 20-30 minutes. The present invention adopts this method to fully dissolve the titanium source in anhydrous ethanol.

[0044] In the present invention, the impregnation is preferably vacuum impregnation. In the present invention, the pressure of the vacuum impregnation is preferably -0.08 to -0.1 MPa, more preferably -0.1 MPa; the temperature of the vacuum impregnation is preferably 20 to 45°C, more preferably 20 to 30°C; the time of the vacuum impregnation is preferably 2 to 4 hours, more preferably 3 to 4 hours. The present invention performs vacuum impregnation under the above conditions, so that the impregnation liquid can be fully immersed in the delignified bamboo specimen.

[0045] In the present invention, the temperature of the transesterification reaction is preferably 100-140°C, more preferably 120-130°C; the time of the transesterification reaction is preferably 3-5h, more preferably 4-5h. The present invention can fully carry out the transesterification reaction of the impregnating liquid immersed in the delignified bamboo specimen at the above temperature and time, and then in situ generate titanium dioxide rich in surface hydroxyl groups on the surface and inside of the delignified bamboo specimen. In the present invention, the device for the transesterification reaction is preferably a reactor.

[0046] The present invention preferably washes and dries the obtained bamboo material in sequence after the transesterification reaction to obtain a titanium dioxide modified bamboo sample. The present invention does not specifically limit the operation method of the washing and drying. Conventional washing and drying methods can be used to fully remove the residual chemical reagents in the bamboo material and dry it. In the present invention, the drying temperature is preferably 30 to 60°C, more preferably 50 to 60°C; the drying time is preferably 6 to 8h, more preferably 7 to 8h. The present invention performs drying at the above temperature and time, which can make the moisture content of the titanium dioxide modified bamboo sample reach 6 to 8%, which is more conducive to promoting the subsequent modification reaction.

[0047] After obtaining the titanium dioxide modified bamboo sample, the present invention mixes the titanium dioxide modified bamboo sample with a hydrophobic modifier to perform hydrophobic modification to obtain the titanium dioxide hydrophobic bamboo sample.

[0048] In the present invention, the hydrophobic modifier preferably includes one or more of octadecyltrimethoxysilane, hexadecyltrimethoxysilane, methyltrimethoxysilane and vinyltrimethoxysilane, and more preferably octadecyltrimethoxysilane. The present invention adopts the above modifier to make the titanium dioxide modified bamboo sample hydrophobic.

[0049] In the present invention, the hydrophobic modifier is preferably mixed with the titanium dioxide modified bamboo sample in the form of a hydrophobic modifier solution. In the present invention, the volume ratio of the hydrophobic modifier to the solvent in the hydrophobic modifier solution is preferably 1:(40-60), more preferably 1:50. The present invention has no special limitation on the solvent, and any solvent that can dissolve the hydrophobic modifier can be used. In an embodiment of the present invention, the solvent of the hydrophobic modifier solution can be n-hexane.

[0050] In the present invention, the temperature of the hydrophobic modification is preferably room temperature; the time of the hydrophobic modification is preferably 4 to 6 hours, more preferably 5 to 6 hours. In the present invention, the hydrophobic modification is preferably carried out under stirring, and the stirring speed is preferably 100 to 200 rpm, more preferably 150 to 200 rpm. Under the above conditions, the present invention can promote the hydrophobic modifier to fully bind to the surface and pores of the titanium dioxide modified bamboo sample.

[0051] After obtaining the titanium dioxide hydrophobic bamboo sample, the present invention preheats the titanium dioxide hydrophobic bamboo sample, and then sequentially performs hot pressing and shaping to obtain a high-strength mildew-proof bamboo material.

[0052] In the present invention, the preheating temperature is preferably 130-160° C., more preferably 140-150° C. The present invention preheats the titanium dioxide hydrophobic bamboo sample, so that the titanium dioxide hydrophobic bamboo sample can be subjected to more uniform force during hot pressing.

[0053] In the present invention, the titanium dioxide hydrophobic bamboo sample is preferably preheated in a hot pressing and qualitative mold. The present invention preheats the titanium dioxide hydrophobic bamboo sample in a hot pressing and qualitative mold, so that the mold and the titanium dioxide hydrophobic bamboo sample are at the same temperature, which is conducive to making the titanium dioxide hydrophobic bamboo sample more uniformly stressed during hot pressing.

[0054] In the present invention, the temperature of the hot pressing is preferably 130-160°C, more preferably 140-150°C; the pressure of the hot pressing is preferably 4-6MPa, more preferably 5-6MPa; in the present invention, the time of the hot pressing is preferably 10-20min, more preferably 15-20min. The present invention performs hot pressing under the above pressure, which can reduce the thickness of the titanium dioxide modified bamboo sample and make its structure dense.

[0055] In the present invention, the shaping method preferably comprises: cooling the hot-pressed titanium dioxide hydrophobic bamboo sample to 40-60° C., preferably 40-45° C. In the present invention, the pressure during the cooling is preferably 4-6 MPa, more preferably 5-6 MPa. In the present invention, the shaping can prevent the hot-pressed titanium dioxide hydrophobic bamboo sample from curling during cooling.

[0056] In the present invention, the compression rate of the high-strength mildew-proof bamboo material is 20-50%, preferably 40-50%. In the present invention, the calculation formula of the compression rate is shown in Formula I:

[0057] Compression ratio = (l 1 -l 2 / l 1 )×100% Formula I

[0058] In Formula I, 1 is the thickness of bamboo, l 2 It is the thickness of high-strength and mildew-resistant bamboo.

[0059] The invention controls the compression rate of the high-strength and mildew-proof bamboo material by controlling the thickness of the thickness gauge at the closed position of the mold during hot pressing. The invention controls the compression rate of the high-strength and mildew-proof bamboo material within the above range, so that the high-strength and mildew-proof bamboo material can maintain a relatively high strength.

[0060] The preparation method provided by the present invention is simple to operate, and utilizes a hot pressing process and a chemical modification method to enable the bamboo material to achieve higher and uniform bending strength at different compression rates, thereby improving the overall mechanical properties of the bamboo material. The present invention forms a highly hydrophobic microstructure by combining a composite treatment technology of titanium dioxide and a hydrophobic agent, thereby reducing the attachment and growth of mold and achieving a lasting anti-mold effect.

[0061] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] Example 1

[0063] A method for preparing high-strength and mildew-resistant bamboo material, comprising the following steps:

[0064] (1) 4-6-year-old fresh bamboo without mold and rot defects was cut into bamboo materials, and the green and yellow bamboo were removed; the bamboo materials (100 mm × 20 mm × 4.5 mm) were placed in a 2% sodium chlorite solution prepared with distilled water, and glacial acetic acid was added to adjust the pH to 4.6; the temperature was raised to 80°C and steamed for 3 hours to remove part of the lignin and hemicellulose in the bamboo materials, with the contents of 20% and 9% respectively; the bamboo materials were then rinsed with deionized water and anhydrous ethanol for multiple times and dried to obtain delignified bamboo specimens;

[0065] (2) tetrabutyl titanate and anhydrous ethanol were mixed in a volume ratio of 1:40 and stirred at 200 rpm for 30 min to obtain an impregnation solution, and the delignified bamboo specimen obtained in the step (1) was immersed in the impregnation solution and vacuum impregnated at 0.1 bar for 4 h, and then the specimen was placed in a reactor and reacted at 110° C. for 4 h, and then the specimen was taken out, and the specimen was washed three times with anhydrous ethanol and deionized water respectively to remove some residual chemical components, and then dried at 45° C. for 8 h to a moisture content of 8%, to obtain a titanium dioxide modified bamboo specimen;

[0066] (3) octadecyltrimethoxysilane and n-hexane are mixed in a volume ratio of 1:50 to obtain a hydrophobic modifier solution; the titanium dioxide modified bamboo sample obtained in step (2) is mixed with the hydrophobic modifier solution, stirred with a magnetic stirrer at 200 rpm for 4 hours for hydrophobic modification, and then washed with n-hexane and anhydrous ethanol solution three times respectively, and then vacuum dried at 45° C. to a moisture content of 8%, to obtain a titanium dioxide hydrophobic bamboo sample;

[0067] (4) The titanium dioxide hydrophobic bamboo sample obtained in step (3) is placed in a hot pressing mold without applying pressure, and is only preheated to a temperature of 140°C. Then, the temperature of the hot press is maintained at 140°C, and the thickness of the mold at the closing position is controlled to be 20% of the original bamboo thickness. The plate pressure (gauge pressure) is 5 MPa and pressed for 15 minutes. The plate temperature is turned off but the pressure is maintained for 2 hours. After the mold temperature is cooled to 50°C, the sample is taken out to obtain a high-strength mildew-proof bamboo material with a compression rate of 20%.

[0068] Example 2

[0069] A method for preparing high-strength and mildew-resistant bamboo material, comprising the following steps:

[0070] (1) 4-6 year old fresh bamboo without mold and rot defects was cut into bamboo materials, and the green and yellow bamboo were removed; the bamboo materials (100 mm × 20 mm × 4.5 mm) were placed in a 2% sodium chlorite solution prepared with distilled water, and glacial acetic acid was added to adjust the pH to 4.6; the temperature was raised to 80°C and steamed for 3 hours to remove part of the lignin and hemicellulose in the bamboo materials, with the contents of 18-22% and 6-10% respectively; the bamboo materials were then rinsed with deionized water and anhydrous ethanol for multiple times and dried to obtain delignified bamboo specimens;

[0071] (2) tetrabutyl titanate and anhydrous ethanol were mixed in a volume ratio of 1:40 and stirred at 200 rpm for 30 min to obtain an impregnation solution, and the delignified bamboo specimen obtained in the step (1) was immersed in the impregnation solution and vacuum impregnated at 0.1 bar for 4 h, and then the specimen was placed in a reactor and reacted at 110° C. for 4 h, and then the specimen was taken out, and the specimen was washed three times with anhydrous ethanol and deionized water respectively to remove some residual chemical components, and then dried at 45° C. for 8 h to a moisture content of 8%, to obtain a titanium dioxide modified bamboo specimen;

[0072] (3) octadecyltrimethoxysilane and n-hexane solution are mixed in a volume ratio of 1:50 to obtain a hydrophobic modifier solution; the titanium dioxide modified bamboo sample obtained in step (2) is mixed with the hydrophobic modifier solution, stirred with a magnetic stirrer at 200 rpm for 4 hours for hydrophobic modification, and then washed with n-hexane and anhydrous ethanol solution three times respectively, and then vacuum dried at 45° C. to a moisture content of 8%, to obtain a titanium dioxide hydrophobic bamboo sample;

[0073] (4) The titanium dioxide hydrophobic bamboo sample obtained in step (3) is placed in a hot pressing mold without applying pressure, and is only preheated to a temperature of 140°C. Then, the temperature of the hot press is maintained at 140°C, and the thickness of the mold at the closing position is controlled to be 30% of the original bamboo thickness. The plate pressure (gauge pressure) is 5 MPa and pressed for 15 minutes. The plate temperature is turned off but the pressure is maintained for 2 hours. After the mold temperature is cooled to 50°C, the sample is taken out to obtain a high-strength mildew-proof bamboo material with a compression rate of 30%.

[0074] Example 3

[0075] A method for preparing high-strength and mildew-resistant bamboo material, comprising the following steps:

[0076] (1) 4-6 year old fresh bamboo without mold and rot defects was cut into bamboo materials, and the green and yellow bamboo were removed; the bamboo materials (100 mm×20 mm×4.5 mm) were placed in a sodium chlorite solution with a mass fraction of 2% prepared by distilled water, and glacial acetic acid was added to adjust the pH to 4.6; the temperature was increased to 80°C and steamed for 2-4 hours to remove part of the lignin and hemicellulose in the bamboo materials, and the contents were 18-22% and 6-10% respectively; then the bamboo materials were rinsed with deionized water and anhydrous ethanol for multiple times and dried to obtain delignified bamboo specimens;

[0077] (2) tetrabutyl titanate and anhydrous ethanol were mixed in a volume ratio of 1:40 and stirred at 200 rpm for 30 min to obtain an impregnation solution, and the delignified bamboo specimen obtained in the step (1) was immersed in the impregnation solution and vacuum impregnated at 0.1 bar for 4 h, and then the specimen was placed in a reactor and reacted at 110° C. for 4 h, and then the specimen was taken out, and the specimen was washed three times with anhydrous ethanol and deionized water respectively to remove some residual chemical components, and then dried at 45° C. for 8 h to a moisture content of 8%, to obtain a titanium dioxide modified bamboo specimen;

[0078] (3) octadecyltrimethoxysilane and n-hexane solution are mixed in a volume ratio of 1:50 to obtain a hydrophobic modifier solution; the titanium dioxide modified bamboo sample obtained in step (2) is mixed with the hydrophobic modifier solution, stirred with a magnetic stirrer at 200 rpm for 4 hours for hydrophobic modification, and then washed with n-hexane and anhydrous ethanol solution three times respectively, and then vacuum dried at 45° C. to a moisture content of 8%, to obtain a titanium dioxide hydrophobic bamboo sample;

[0079] (4) The titanium dioxide hydrophobic bamboo sample obtained in step (3) is placed in a hot pressing mold without applying pressure, and is only preheated to a temperature of 140°C. Then, the temperature of the hot press is maintained at 140°C, and the thickness of the mold at the closed position is controlled to be 40% of the original bamboo thickness. The plate pressure (gauge pressure) is 5 MPa and pressed for 15 minutes. The plate temperature is turned off but the pressure is maintained for 2 hours. After the mold temperature is cooled to 50°C, the sample is taken out to obtain a high-strength mildew-proof bamboo material with a compression rate of 40%.

[0080] Example 4

[0081] A method for preparing high-strength and mildew-resistant bamboo material, comprising the following steps:

[0082] (1) 4-6 year old fresh bamboo without mold and rot defects was cut into bamboo materials, and the green and yellow bamboo were removed; the bamboo materials (100 mm × 20 mm × 4.5 mm) were placed in a 2% sodium chlorite solution prepared with distilled water, and glacial acetic acid was added to adjust the pH to 4.6; the temperature was raised to 80°C and steamed for 3 hours to remove part of the lignin and hemicellulose in the bamboo materials, with the contents of 18-22% and 6-10% respectively; the bamboo materials were then rinsed with deionized water and anhydrous ethanol for multiple times and dried to obtain delignified bamboo specimens;

[0083] (2) tetrabutyl titanate and anhydrous ethanol were mixed in a volume ratio of 1:40, stirred at 200 rpm for 30 min to obtain an impregnation solution, and the delignified bamboo specimen obtained in step (1) was immersed in the impregnation solution, and vacuum impregnated at 0.1 bar for 2-4 h, and then the specimen was placed in a reactor and reacted at 110° C. for 4 h, and then the specimen was taken out, and the specimen was washed three times with anhydrous ethanol and deionized water respectively to remove some residual chemical components, and then dried at 45° C. for 8 h to a moisture content of 8%, to obtain a titanium dioxide modified bamboo specimen;

[0084] (3) octadecyltrimethoxysilane and n-hexane solution are mixed in a volume ratio of 1:50 to obtain a hydrophobic modifier solution; the titanium dioxide modified bamboo sample obtained in step (2) is mixed with the hydrophobic modifier solution, stirred with a magnetic stirrer at 200 rpm for 4 hours for hydrophobic modification, and then washed with n-hexane and anhydrous ethanol solution three times respectively, and then vacuum dried at 45° C. to a moisture content of 8%, to obtain a titanium dioxide hydrophobic bamboo sample;

[0085] (4) The titanium dioxide hydrophobic bamboo sample obtained in step (3) is placed in a hot pressing mold without applying pressure, and is only preheated to a temperature of 140°C. Then, the temperature of the hot press is maintained at 140°C, and the thickness of the mold at the closing position is controlled to be 50% of the original bamboo thickness. The plate pressure (gauge pressure) is 5 MPa and pressed for 15 minutes. The plate temperature is turned off but the pressure is maintained for 2 hours. After the mold temperature is cooled to 50°C, the sample is taken out to obtain a high-strength mildew-proof bamboo material with a compression rate of 50%.

[0086] Comparative Example 1

[0087] A method for preparing bamboo material: cutting 4-6 year old fresh bamboo material without mildew and rot defects into bamboo material, and removing bamboo green and bamboo yellow to obtain bamboo material (50mm×20mm×4.5mm).

[0088] Comparative Example 2

[0089] A method for preparing high-strength and mildew-resistant bamboo material, comprising the following steps:

[0090] (1) 4-6 year old fresh bamboo without mold and rot defects was cut into bamboo materials, and the green and yellow bamboo were removed; the bamboo materials (50 mm × 20 mm × 4.5 mm) were placed in a 2% sodium chlorite solution prepared by distilled water, and glacial acetic acid was added to adjust the pH to 4.6; the temperature was raised to 80°C and steamed for 3 hours to remove part of the lignin and hemicellulose in the bamboo materials, with the contents of 18-22% and 6-10% respectively; the bamboo materials were then rinsed with deionized water and anhydrous ethanol for multiple times and dried to obtain delignified bamboo specimens;

[0091] (2) Tetrabutyl titanate and anhydrous ethanol are mixed in a volume ratio of 1:40 and stirred at 200 rpm for 30 minutes to obtain an impregnation solution. The delignified bamboo specimen obtained in the step (1) is immersed in the impregnation solution and vacuum impregnated at 0.1 bar for 4 hours. The specimen is then placed in a reactor and reacted at 110° C. for 4 hours. The specimen is then taken out and washed three times with anhydrous ethanol and deionized water respectively to remove some residual chemical components. The specimen is then dried at 45° C. for 8 hours until the moisture content is 8%, thereby obtaining a titanium dioxide modified bamboo specimen.

[0092] Comparative Example 3

[0093] A method for preparing bamboo material: cutting 4-6 year old fresh bamboo material without mildew and rot defects into bamboo material, removing bamboo green and bamboo yellow, and obtaining bamboo material (100mm×20mm×4.5mm).

[0094] Test Case

[0095] (1) Mildew resistance: According to the Chinese standard GB / T 18261-2013 "Test method for the control of wood mildew and blue stain fungi by mildew inhibitors", Aspergillus niger (mildew) and Trichoderma viride (mildew) were used for a 30-day laboratory-scale antifungal test on the surfaces of the control group, i.e., the bamboo material (50 mm×20 mm×4.5 mm) obtained in Comparative Example 1, the titanium dioxide hydrophobic bamboo sample (50 mm×20 mm×4.5 mm) obtained in Comparative Example 2, and the high-strength mildew-resistant bamboo material (50 mm×20 mm×2.7 mm) with a compression rate of 40% prepared in Example 3. Each treatment group was repeated at least six times to evaluate its mildew resistance.

[0096] The antifungal performance of high-strength and mildew-resistant bamboo is evaluated according to Formula II.

[0097]

[0098] In formula II: E is the control effect (%); D1 is the average infection area of ​​the treated samples; D2 is the average infection area of ​​the control samples.

[0099] The results of Aspergillus niger control show that the control efficiency of the bamboo material obtained in Comparative Example 1 is 0%; the control efficiency of the titanium dioxide hydrophobic bamboo sample obtained in Comparative Example 2 is 96%; the control efficiency of the high-strength mildew-proof bamboo material with a compression rate of 40% prepared in Example 3 is 100%;

[0100] The results of green Trichoderma control show that the control effect of the bamboo obtained in Comparative Example 1 is 0%; the control effect of the titanium dioxide hydrophobic bamboo sample obtained in Comparative Example 2 is 90%; the control effect of the high-strength mildew-proof bamboo with a compression rate of 40% prepared in Example 3 is 100%;

[0101] Surface wettability (contact angle): The contact angle of the bamboo material obtained in Comparative Example 1 is 39°; the contact angle of the titanium dioxide hydrophobic bamboo sample obtained in Comparative Example 2 is 133°; the contact angle of the high-strength mildew-proof bamboo material with a compression rate of 40% prepared in Example 3 is 141°.

[0102] (2) Mechanical properties: According to the Chinese national standard GB / T 1927.10-2021 "Test methods for physical and mechanical properties of small defect-free specimens of wood - Part 10: Determination of flexural elastic modulus", a universal testing machine was used to test the modulus of rupture (MOR) and modulus of elasticity (MOE) of the bamboo material obtained in Comparative Example 3 (100 mm × 20 mm × 4.5 mm); the high-strength mildew-proof bamboo material with a compression rate of 20% prepared in Example 1 (100 mm × 20 mm × 3.6 mm); the high-strength mildew-proof bamboo material with a compression rate of 30% prepared in Example 2 (100 mm × 20 mm × 3.15 mm); the high-strength mildew-proof bamboo material with a compression rate of 40% prepared in Example 3 (100 mm × 20 mm × 2.7 mm); and the high-strength mildew-proof bamboo material with a compression rate of 50% prepared in Example 4 (100 mm × 20 mm × 2.25 mm). Before the test, the dimensions of all samples were measured with a digital caliper, and six samples were taken from each group of bamboo for a three-point bending test to calculate the MOR and MOE of the samples.

[0103] The results of the three-point bending test are as follows:

[0104] MOR: The bamboo material obtained in Comparative Example 3 is 143MPa; the high-strength mildew-resistant bamboo material with a compression rate of 20% prepared in Example 1 is 166MPa; the high-strength mildew-resistant bamboo material with a compression rate of 30% prepared in Example 2 is 194MPa; the high-strength mildew-resistant bamboo material with a compression rate of 40% prepared in Example 3 is 225MPa; the high-strength mildew-resistant bamboo material with a compression rate of 50% prepared in Example 4 is 203MPa;

[0105] MOE: The bamboo material obtained in Comparative Example 3 is 8.7 GPa; the high-strength mildew-resistant bamboo material with a compression rate of 20% prepared in Example 1 is 11.4 GPa; the high-strength mildew-resistant bamboo material with a compression rate of 30% prepared in Example 2 is 12.6 GPa; the high-strength mildew-resistant bamboo material with a compression rate of 40% prepared in Example 3 is 17.1 GPa; the high-strength mildew-resistant bamboo material with a compression rate of 50% prepared in Example 4 is 13.7 GPa.

[0106] It can be seen from the above results that the high-strength mildew-proof bamboo material prepared by the present invention has excellent mildew-proof effect and mechanical properties. This is because the present invention uses hot pressing process and chemical modification method to make bamboo material achieve higher and uniform bending strength at different compression rates, and improve the overall mechanical properties of bamboo material. In addition, this modification process effectively avoids the brittleness problem that may be caused by traditional treatment methods, and improves the durability and stability of bamboo material. The present invention forms a microstructure with high hydrophobicity by combining the composite treatment technology of titanium dioxide and hydrophobic agent, reduces the attachment and growth of mold, achieves a lasting mildew-proof effect, and prolongs the service life of bamboo material. At the same time, the durability of the formed composite hydrophobic layer enhances the performance of bamboo material in a humid environment, and the hydrophobic layer formed by the self-assembly of the hydrophobic agent effectively reduces the attachment of dirt, keeps the surface clean, and further improves the self-cleaning effect. The present invention adopts a treatment method of environmentally friendly materials, reduces the pollution that may be caused to the environment in traditional chemical treatment methods, and uses a more environmentally friendly treatment method; the modified bamboo material shows good long-term stability in daily use environment, and improves the durability and reliability of the material.

[0107] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing high-strength and mildew-resistant bamboo material, comprising the following steps: (1) removing part of the lignin and hemicellulose from the bamboo to obtain a delignified bamboo specimen; (2) immersing the delignified bamboo specimen obtained in step (1) in an immersion solution, and then performing an ester exchange reaction to obtain a titanium dioxide-modified bamboo specimen; the immersion solution is a solution composed of a titanium source and anhydrous ethanol; (3) mixing the titanium dioxide modified bamboo sample obtained in step (2) with a hydrophobic modifier to perform hydrophobic modification to obtain a titanium dioxide hydrophobic bamboo sample; (4) preheating the titanium dioxide hydrophobic bamboo sample obtained in step (3), and then hot pressing and shaping in sequence to obtain a high-strength and mildew-proof bamboo material; the compression rate of the high-strength and mildew-proof bamboo material is 20-50%.

2. The method for preparing high-strength and mildew-resistant bamboo material according to claim 1, characterized in that: The method for removing part of lignin and hemicellulose from bamboo in step (1) comprises: removing green bamboo and yellow bamboo from fresh bamboo to obtain bamboo; placing the bamboo in a sodium chlorite solution with a pH value of 4 to 5 and performing heat treatment to obtain a delignified bamboo specimen.

3. The method for preparing high-strength and mildew-resistant bamboo material according to claim 1, characterized in that: The titanium source in step (2) includes one or more of tetrabutyl titanate, tetraisopropyl titanate and tetraethyl titanate.

4. The method for preparing high-strength and mildew-resistant bamboo material according to claim 1 or 3, characterized in that: In the step (2), the volume ratio of the titanium source to anhydrous ethanol is 1:(30-50).

5. The method for preparing high-strength and mildew-resistant bamboo material according to claim 1, characterized in that: The temperature of the transesterification reaction in step (2) is 100 to 140° C., and the time of the transesterification reaction is 3 to 5 hours.

6. The method for preparing high-strength and mildew-resistant bamboo material according to claim 1, characterized in that: The hydrophobic modifier in step (3) includes one or more of octadecyltrimethoxysilane, hexadecyltrimethoxysilane, methyltrimethoxysilane and vinyltrimethoxysilane.

7. The method for preparing high-strength and mildew-resistant bamboo material according to claim 1, characterized in that: The temperature of the hydrophobic modification in step (3) is 20 to 45° C., and the time of the hydrophobic modification is 4 to 6 hours.

8. The method for preparing high-strength and mildew-resistant bamboo material according to claim 1, characterized in that: The preheating temperature and the hot pressing temperature in step (4) are 130-160°C.

9. The method for preparing high-strength and mildew-resistant bamboo material according to claim 1, characterized in that: The hot pressing pressure in step (4) is 4-6 MPa, and the hot pressing time is 10-20 min.

10. The method for preparing high-strength and mildew-resistant bamboo material according to claim 1 or 9, characterized in that: The shaping method in step (4) comprises: cooling the hot-pressed titanium dioxide hydrophobic bamboo sample to 40-60° C., wherein the pressure during cooling is 4-6 MPa.